Networks of (dis)trust the impact of automation, corruption, and media on Philippine elections - Reyes Jr., Vicente Chua 1968- (Lexington Books, 2019)
"This book reviews dominant paradigms of the Philippine state trapped in a simplistic patronage politics perspective. Using the unprecedented automation of the May 2010 elections. this book provides fresh theoretical perspectives in understanding the Philippine state as a complex assemblage of networks of distrust"--Provided by publisher.